2017
DOI: 10.24953/turkjped.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Rational drug use for acute bronchiolitis in emergency care

Abstract: Despite the large variety of inhaled treatment options of acute bronchiolitis, there is no generally agreed treatment regime. This study aimed to determine the most appropriate treatment option. This was a double-blind randomized prospective clinical trial and has been performed in emergency department. The mean age of the 378 infants included in the study was 7.63 ± 4.6 months, and 54.8% (207) were boys. Patients were randomized by using the lottery method for simple random sample into 5 different treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…No side effects requiring intervention were observed in any of the preoperative cohort. This supports the hypothesis that epinephrine nebulization is an intervention with minimal side effects, as has already been documented in the human literature 10,12,16‐17 . The main side effect was nausea, which may have been induced by stress associated with nebulization or, alternatively, may have been a side effect of the epinephrine itself.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…No side effects requiring intervention were observed in any of the preoperative cohort. This supports the hypothesis that epinephrine nebulization is an intervention with minimal side effects, as has already been documented in the human literature 10,12,16‐17 . The main side effect was nausea, which may have been induced by stress associated with nebulization or, alternatively, may have been a side effect of the epinephrine itself.…”
Section: Discussionsupporting
confidence: 88%
“…This supports the hypothesis that epinephrine nebulization is an intervention with minimal side effects, as has already been documented in the human literature. 10,12,[16][17] The main side effect was nausea, which may have been induced by stress associated with nebulization or, alternatively, may have been a side effect of the epinephrine itself. Most dogs that became nauseous were known to regurgitate previously, attributed to their BOAS; however, one dog that became nauseous had no history of regurgitation, so the side effect in this dog was likely directly related to nebulization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A randomized double-blind trial from Turkey showed no statistical difference between nebulized epinephrine and salbutamol in terms of discharge rate at 24 hours, however adrenaline with 3% hypertonic helped reduce the length of stay (p=0.039). 12 Racemic epinephrine was compared with hypertonic saline in terms of length of stay by Yasin F et al 13 and found epinephrine effective in reducing the length of stay in patients with moderate bronchiolitis. However, some contrasting results were also in literature, where researchers demonstrated equal effectiveness of salbutamol and epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…We decided not to carry out a metaanalysis of safety data due to a small number of events and show a very low rate of mild adverse events during or post nebulization (1%) and no patient was withdrawn from the study due to side effects. One trial 23 reported a total frequency of 5.5% of adverse events (including tachycardia, pallor, tremor, nausea, and vomiting), but rates were not significantly different when comparing intervention and control groups. Pandit et al 38 reported four mild events (4%) in the 0.9% saline plus epinephrine group (three vomiting and one diarrhea).…”
Section: Safety Profilementioning
confidence: 99%